Association Between Immunization Status and Complete Nutrition Provision with Wasting Incidence in Toddlers - Liwu, Desilia Sidong; Zulaikha, Fatma; Asthiningsih, Ni Wayan Wiwin (Inspirasi Foundation, 2025)
Introduction : Wasting is a condition of acute malnutrition in toddlers, where body weight is below normal standards (z-score -3 SD to < -2 SD). This condition can occur due to lack of nutrition and incomplete immunization. Objective : This study aims to determine the relationship between immunization status and provision of complementary foods to the incidence of wasting in toddlers at the Sidomulyo Health Center, Samarinda. Research Method : This study used a quantitative correlational design with a cross-sectional approach. Result : The sample consisted of 188 toddlers aged 2-5 years who were taken stratified. Data were collected using a questionnaire and analyzed using the Chi-Square test. The results obtained There is a significant relationship between immunization status and provision of complementary foods with the incidence of wasting (p-value < 0.05). Toddlers with incomplete immunization have a higher risk of wasting (OR = 0.3 2 ). Conclusion : Toddlers who are given complementary foods <6 months also show a higher prevalence of wasting (OR = 8.94). Complete immunization status and provision of complementary foods on time are important factors in preventing wasting in toddlers.